PELATIHAN PENERAPAN PENCEGAHAN ISPA, HIPERTENSI DAN PHBS DI DUSUN V BANJARAN KECAMATAN BIRU-BIRU TAHUN 2019 - Rawalven Purba; Fithri Handayani Lubis; Ripai Siregar; Sulastri Ginting (INSTITUT KESEHATAN DELI HUSADA, 2021)
Nowadays, health problems are not only in the form of infectious diseases but also non-communicable diseases that arise from unhealthy lifestyles and poor environmental conditions. Health problems in the form of communicable and non-communicable diseases originate from the lack of implementation of preventive and promotive measures. Health problems that become a problem are acute respiratory infections and hypertension. Increasing health problems such as acute respiratory infections and hypertension can be prevented by increasing promotive and preventive efforts for the community. Preventive measures are carried out by avoiding risk factors for disease. The purpose of this service is to improve primary health services in the community of Dusun V Banjaran, Kecamatan Biru-Biru in order to achieve an optimal quality of life. This service was carried out for 211 families and 20 elderly people in Dusun V Banjaran, Blue-Biru District, Deli Serdang Regency. Community service activities are directed at overcoming the problem of lack of clean and healthy living habits (PHBS) which results in acute respiratory infections and hypertension. The implementation of activities consists of assessment and health education, medical examinations, gymnastics and progressive muscle relaxation exercises for hypertensive elderly. The impact of this community service activity is awareness of health problems by residents so that residents have the awareness to overcome problems by empowering themselves through available resources such as health knowledge and skills and utilizing existing health facilities.